Role of Fintech in Enhancing Credit Usage Among the Un(der)-Banked - Ntwiga, Davis (Academia Kenya, 2021)
The un(der)-banked lack financial histories and financial strength to be attractive to financial institutions, and this limits their ability to access credit. In 2015, around 36.1 percent of Kenyans were classified as poor. Access to micro- credit loans through financial technology (Fintech) can promote individual outcomes while contributing to several of the United Nations’ Sustainable Development Goals (Hove and Dubus, 2019). Some of the un(der)-banked perceive technology to be risky and not easy to use. A study in 2016 found that M-Pesa had lifted 2 percent of Kenyans out of poverty and reduced the unbanked population (Hove and Dubus, 2019). A Financial Access Household Survey in 2016 noted that individuals seek financial products that cater to their small and inconsistent incomes, offer better tools for managing day to day transactions and risks, while supporting them to face major life transitions (FSD, 2016). This profile of consumers requires an innovative approach, for example, through the use of big data and artificial intelligence deployed by Fintech firms, to cater for their lack of financial histories in the credit lending process. The availability of soft information means that Fintech can cater for this market gap to further enhance financial inclusion if vibrant, competitive and sound credit market practices are introduced and enforced.
Keywords: Kenya; Fintech